2015
DOI: 10.1371/journal.pntd.0003937
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Dengue in a Brazilian Urban Slum Setting: Role of Socioeconomic Gradient in Disease Risk

Abstract: BackgroundFew studies of dengue have shown group-level associations between demographic, socioeconomic, or geographic characteristics and the spatial distribution of dengue within small urban areas. This study aimed to examine whether specific characteristics of an urban slum community were associated with the risk of dengue disease.Methodology/Principal FindingsFrom 01/2009 to 12/2010, we conducted enhanced, community-based surveillance in the only public emergency unit in a slum in Salvador, Brazil to identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
116
2
14

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(137 citation statements)
references
References 51 publications
5
116
2
14
Order By: Relevance
“…Various studies have attempted to identify risk areas in cities and their social and environmental determinants 22,23,24,25,26,27,42 , producing controversial results, that is, some indicating poor neighborhoods as risk areas for dengue, and others the opposite, with wealthier areas as the riskiest 24,43 . This disparity of results may be the consequence of the spatial-temporal dynamics of dengue epidemics themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have attempted to identify risk areas in cities and their social and environmental determinants 22,23,24,25,26,27,42 , producing controversial results, that is, some indicating poor neighborhoods as risk areas for dengue, and others the opposite, with wealthier areas as the riskiest 24,43 . This disparity of results may be the consequence of the spatial-temporal dynamics of dengue epidemics themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Dengue thrives in urban slums, as indicated by a study based on community-based surveillance in a slum in Salvador, Brazil which found 22% of febrile patients with evidence of dengue infection. The study also suggested that socioeconomic development could potentially mitigate risk factors for both dengue and non-dengue febrile cases, and found that residential proximity to a health care facility was associated with improved case detection [141]. …”
Section: Main Textmentioning
confidence: 99%
“…The burden of symptomatic dengue, another mosquito-borne disease, has been shown to be greater among the neighborhoods with the lowest socioeconomic status within a slum [4]. In a study of successive dengue epidemics in Rio de Janeiro that occurred in 2007 and 2008, Rosa-Freitas et.…”
mentioning
confidence: 99%